Stereoselective synthesis of 1,6-diazecanes by a tandem aza-Prins type dimerization and cyclization process - Kim, Gyeong Un; Cho, Hyunmi; Lee, Jae Kyun; Lee, Jae Yeol; Tae, Jinsung; Min, Sun-Joon; Kang, Taek; Cho, Yong Seo (Royal Society of Chemistry, 2023)
We report the stereocontrolled synthesis of 1,6-diazecanes via a tandem aza-Prins type reaction of N-acyliminium ions with allylsilanes. It involves an aza-Prins type dimerization and cyclization in a single-step operation. This reaction represents the first example of 10-membered N-heterocycle synthesis using an aza-Prins reaction. Also, the interesting formation of an unusual tetracyclic compound through further cyclization of 1,6-diazecane and bicyclic compounds by the intramolecular cyclization of linear allylsilane are described. This tandem aza-Prins protocol provides a new synthetic strategy for the direct synthesis of medium-sized nitrogen heterocycles.